(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: To describe the prevalence of acne among junior high school students in Hanoi in 2022 and related factors. Subjects and methods: A cross-sectional study was carried out among 1751 students aged 11-15 at four secondary schools in Hanoi City. Study subjects were interviewed faceto-face using structured questionnaires. Dermatologists also checked them. Classification of the severity of acne was following Karen McKoy’s scale (2008). Results: The prevalence of acne in the study subjects was 21.7%, strongly associated with age and gender (26.2% of girls and 17.7% of boys). The main risk factors of acne were puberty (OR=2.82; 95%CI: 2.04-3.90) and oily and combination skin (OR=1.90; 95%CI: 1.48-2.43). No statistically significant association was found between family history, acquired diseases, eating and living habits, and acne status. Conclusion: The prevalence of acne in junior high school students was relatively high (21.7%). Factors such as puberty, oily, and combination skin were high-risk factors for acne in students.